Pendampingan Kelompok Tani Bangsring Jaya dalam Pembuatan Pupuk Organik Berbahan Kotoran Sapi di Desa Bangsring Kabupaten Banyuwangi - Effendi, Mokhtar; Indraloka, Aldy Bahaduri; Shidiqi, Moh Hasbi Ash; Mudhor, Mohammad Ali (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2025)
Fertilizers are a key component in agriculture, supporting soil fertility and enhancing crop productivity. However, the scarcity of subsidized fertilizers often poses significant challenges for farmers in meeting the nutritional needs of their crops, ultimately affecting yields and farmers' economic well-being. On the other hand, cattle manure waste remains largely underutilized. This waste is often left to accumulate in livestock enclosures or discarded without proper treatment. Processing cattle manure into organic fertilizer can not only mitigate the negative environmental impacts of waste but also offer an alternative solution to the shortage of subsidized fertilizers. The objective of this community service program is to assist farmer groups in producing organic fertilizer from cattle manure, with the aim of improving farmers' knowledge and skills in waste management and organic fertilizer production. Furthermore, this initiative seeks to support food security and promote sustainable agricultural productivity in Bangsring Village, Banyuwangi Regency. The program has successfully reduced farmers’ dependence on subsidized fertilizers and contributed to increased crop yields. Pupuk merupakan komponen utama dalam pertanian yang mendukung kesuburan tanah dan meningkatkan produktivitas tanaman. Namun, kelangkaan pupuk bersubsidi seringkali mengakibatkan petani menghadapi kesulitan dalam memenuhi kebutuhan nutrisi tanaman mereka, yang pada akhirnya memengaruhi hasil panen dan kesejahteraan ekonomi petani. Di sisi lain, ada permasalahan limbah kotoran sapi yang belum diolah secara optimal. Limbah ini seringkali dibiarkan mengendap di kandang ternak atau dibuang tanpa pengolahan yang tepat. Pengolahan kotoran sapi untuk diolah sebagai pupuk organik tidak hanya dapat mengurangi dampak negatif dari limbah, tetapi juga memberikan alternatif solusi bagi kelangkaan pupuk bersubsidi. Tujuan pengabdian masyarakat adalah pendampingan kelompok tani dalam pembuatan pupuk organik berbahan kotoran sapi sehingga diharapkan untuk meningkatkan pemahaman dan keterampilan petani dalam mengolah limbah menjadi pupuk organik. Adapun itu, program ini juga bertujuan untuk mendukung ketahanan pangan dan meningkatkan produktivitas pertanian secara berkelanjutan di Desa Bangsring Kabupaten Banyuwangi. Program ini telah berhasil mengurangi ketergantungan petani terhadap pupuk bersubsidi dan meningkatkan hasil panen.